Sleep Disturbance in Bipolar Disorder: Neuroglia and Circadian Rhythms - Steardo, Luca; de Filippis, Renato; Carbone, Elvira Anna; Segura-Garcia, Cristina; Verkhratsky, Alexei; De Fazio, Pasquale (Frontiers in Psychiatry, 2019)
The worldwide prevalence of sleep disorders is ~ 50% with even higher occurrence in psychiatric population. Bipolar disorder (BD) is a severe mental illness characterized by shifts in mood and activity. The BD syndrome also involves heterogeneous symptomatology including cognitive dysfunctions and impairments of autonomic nervous system. Sleep abnormalities are frequently associated with BD and are often a good predictor of a mood swing. Preservation of stable sleep–wake cycles is therefore a key to the maintenance of stability in BD indicating also the crucial role of circadian rhythms in this syndrome. The symptom most widespread in BD is insomnia, followed by excessive daytime sleepiness, nightmares, difficulty falling asleep or maintaining sleep, poor sleep quality, sleep talking, sleep walking and obstructive sleep apnea. Alterations in the structure or duration of sleep are reported in all phases of BD. Understanding the role of neuroglia in BD and in various aspects of sleep are in nascent state. Contributions of the different types of glial cells to BD and sleep abnormalities are discussed in this paper.